Below the Belt? Territory and Development in China's International Rise. Issue 1 (8th August 2020) - Mohan, Giles
ABSTRACT: China's internationalization has been heralded by some as a new era of South–South cooperation. Yet such framings of development are pitched at an abstract space of the 'global South' which conceals more than it reveals. With some theory moving towards ontologies of 'global development', we need to capture both the connectedness and the local specificity of increasingly diffuse processes. This article sets out a more fine‐grained understanding of how political territories and processes are imagined and produced by and through China's internationalization, focusing on infrastructure as a 'technology' of territorialization. Much of the focus on China's internationalization has been on state‐to‐state relations, but this obscures the 'omni‐channel politics' that China practises. Using a critical literature review and illustrative case study, this article develops the idea of omni‐channel politics to posit a view of 'twisted' territories in which political processes and development outcomes are more complex and contingent.